The Influence of FinTech and Banks Collaboration towards Banks Performance: Indonesian Banks Listed - Kurniawati, Regina Zaviera Anggi (APPS Publications, 2022)
The rapid growth of the technology industry has created opportunities to expand businesses such as financial technology. The number of financial technologies is continuously increasing, and this has a variety of consequences for similar businesses. Fintech is claimed to be causing disruption or providing new opportunities for banks to expand their operations. As a result, this study will investigate the influence of fintech and bank collaboration because they both provide financial services. This study will examine 36 banks in Indonesia consisting of 72 samples for the 2019-2020 period. According to the findings of this study, there is no significant influence of bank and fintech collaboration on bank performance. This research will contribute to examining the role of digital financial innovation in the banking sector. Furthermore, banks can use it as a guide to understand the risks and possibilities associated with fintech.